Enhancing ethanol production from thermophilic and mesophilic solid digestate using ozone combined with aqueous ammonia pretreatment. (May 2016) - Wang, Dianlong; Xi, Jiang; Ai, Ping; Yu, Liang; Zhai, Hong; Yan, Shuiping; Zhang, Yanlin
Highlights: Recover residual organic carbon from solid digestate to produce ethanol. Pre-treat recalcitrant solid digestate using combined ozone with aqueous ammonia. Elucidate a combined and successive utilization of lignocelluloses. Abstract: Pretreatment with ozone combined with aqueous ammonia was used to recover residual organic carbon from recalcitrant solid digestate for ethanol production after anaerobic digestion (AD) of rice straw. Methane yield of AD at mesophilic and thermophilic conditions, and ethanol production of solid digestate were investigated. The results showed that the methane yield at thermophilic temperature was 72.2% higher than that at mesophilic temperature under the same conditions of 24 days and 17% solid concentration. And also the ethanol production efficiency of solid digestate after thermophilic process was 24.3% higher than that of solid digestate after mesophilic process. In this study, the optimal conditions for integrated methane and ethanol processes were determined as 55 °C, 17% solid concentration and 24 days. 58.6% of glucose conversion, 142.8 g/kg of methane yield and 65.2 g/kg of ethanol yield were achieved, and the highest net energy balance was calculated as 6416 kJ/kg.